2001
DOI: 10.1902/jop.2001.72.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Chronic Adult Periodontitis Analyzed by In Situ DNA Breaks, Electron Microscopy, and Immunohistochemistry

Abstract: Our findings establish that apoptosis is induced in the periodontal tissue by host and microbial factors and support the hypothesis that apoptotic mechanisms could be implicated in the inflammatory process associated with gingival tissue destruction observed in adult periodontitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
95
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 49 publications
10
95
1
5
Order By: Relevance
“…FGFs and fibroblast growth factor receptors (FGFRs) are key players in the processes of fibroblast proliferation and differentiation of gingival tissues [36][37][38]. Bcl family members act as anti-or pro-apoptotic regulators, which are involved in a wide variety of cellular activities [39][40]. RANKL is a critical factor required in the processing of alveolar bone resorption [41].…”
Section: Discussionmentioning
confidence: 99%
“…FGFs and fibroblast growth factor receptors (FGFRs) are key players in the processes of fibroblast proliferation and differentiation of gingival tissues [36][37][38]. Bcl family members act as anti-or pro-apoptotic regulators, which are involved in a wide variety of cellular activities [39][40]. RANKL is a critical factor required in the processing of alveolar bone resorption [41].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of cells through infection-induced apoptosis is widely recognized as contributing to gastritis (21,32). A similar process may be important in periodontal disease, where it has been shown that apoptosis of fibroblasts is enhanced (12,24,26,34,40). It has also recently been reported that apoptosis of fibroblastic cells is associated with loss of attachment (11).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence for the presence of apoptotic cells in periodontitis (19,34,51,57). Therefore, understanding the mechanisms of endothelial apoptosis induction in the periodontal pocket by P. gingivalis could provide new therapeutic targets of periodontitis and insights into the relationship between P. gingivalis and cardiovascular disease.…”
mentioning
confidence: 99%